The use of gambir as coloring agent in dyeing of cotton textile - Lukas, Amos (Jurnal Dinamika Penelitian Industri, 2011)
The objective of this research was to study the use of gambir as coloring agent on cottonÂ fabric by using specific dipping condition and to obtain the best gambir concentration.Â Concentrations of gambir solution used in this study were 7.5, 12.5, 17.5, and 22.5 g/l,Â respectively. Dipping process was started by soaking of cotton fabric in gambir solution forÂ 15 minutes at 40â100 Â°C temperature which was subsequently dried and put in roomÂ temperature for 15 minutes. The fixation process was repeated seven times using 5%Â weight/volume of calcium hydroxide for 15 minutes. The results showed that grey scale forÂ colorfastness was in the range of 1 to 3. Coloring scale in cotton fabric was in the range of3.5 to 4.5 and it was 4 to 5 on polyesther fabric. Coloring scale on dry ironing was in theÂ range of 4 to 5 and it was 2.5 to 4 on wet ironing. The L* value was in the range of 40.5 toÂ 64.84, a* value was in the range of 10.71 to 19.76 and b* value was in the range of 16.99Â to 24.51. The best concentration of gambir solution was 2.5% with L* value of 64.84, *Â value of 12.04 and b* value of 17.38. The grey scale was 3, coloring scale on cotton andÂ polyesther fabrics was 5, coloring scale for dry ironing was 5 and coloring scale for wetÂ ironing was 4.Keywords: Gambir, coloring agent, cotton fabric, coloring scale, concentrationÂ AbstrakPenelitian ini bertujuan untuk mempelajari penggunaan gambir sebagai bahan pewarnaÂ pada kain kapas dengan kondisi percelupan tertentu dan mendapatkan konsentrasiÂ gambir yang terbaik. Konsentrasi larutan gambir yang digunakan adalah 7,5; 12,5; 17,5;Â 22,5 (g/l). Proses pencelupan dimulai dengan perendaman kain kapas dalam larutanÂ gambir selama 15 menit, suhu di 40â100 Â°C, kemudian dikeringkan dan diletakkan padaÂ suhu kamar selama 10 menit. Proses pengulangan fiksasi sampai tujuh kali dengan 5%Â b/v kalsium hidroksida selama 15 menit. Hasil penelitian menunjukkan bahwa skala abuabuÂ untuk color fastness berkisar antara 1â3. Skala pewarnaan pada kapas berkisarÂ antara 3,5â4,5, sedangkan pada poliester berkisar antara 4â5. Pewarnaan skala untukÂ menggosok kering berkisar 4â5; untuk menggosok basah berkisar antara 2,5â4. Nilai L*Â berkisar antara 40,5â64,84, nilai a* berkisar antara 10,71â19,76, dan nilai b* berkisarÂ antara 16,99â24,51. Konsentrasi terbaik larutan gambir adalah 2,5% dengan nilai L*Â adalah 64,84, nilai a* adalah 12,04; b* adalah 17,38. Skala Grey adalah 3. SkalaÂ pewarnaan pada kapas dan polyester adalah 5. Skala Pewarnaan dalam menggosokÂ kering adalah 5, dan menggosok basah adalah 4.Kata Kunci: gambir, pewarna, kain kapas, skala pewarnaan, konsentrasi